Impact of Project Management Methodologies on IT Software Project Outcomes - Tkachev, Arseniy (2024)
This thesis investigates the impact of project management methodologies on Information Technology (IT) software development project outcomes, focusing on Traditional Project Management (TPM) and Agile Project Management (APM) approaches. The motivation is to understand how these methodologies influence success metrics such as time, cost, quality, stakeholder satisfaction, and business value across various IT projects. The study involves two practical case studies: a Sales Analyzer Application, a software development project that employs Waterfall methodology, and a Serialization project employing Agile. The analysis investigates how each methodology addresses project constraints, requirements, and objectives. The ultimate goal is to identify conditions where specific approaches perform exceptionally well. The case studies present insights from observing the project execution and success metrics.